Dynamic Interactions: Macro Factors and Composite Index: 2017-2021 Evidence: Interaksi Dinamis: Faktor Makro dan Indeks Komposit: Bukti Empiris 2017-2021 - Tasya May Fatmala; Misti Hariasih (Universitas Muhammadiyah Sidoarjo, 2023)
This research investigates the impact of inflation, interest rates, and exchange rates on the Composite Index (JCI) through quantitative methods and secondary data analysis. Utilizing a saturated sample method over a five-year period (2017-2021) with 60 monthly observations, the study employs multiple linear regression analysis using EViews 9. The findings reveal that inflation has a positive yet insignificant effect on the JCI, while interest rates exert a positive and significant influence. Additionally, exchange rates display a negative and significant impact on the JCI. Notably, the simultaneous presence of inflation, interest rates, and exchange rates significantly affects the JCI. The results contribute to the understanding of the intricate dynamics between macroeconomic factors and stock market performance, offering valuable insights for investors, policymakers, and market participants worldwide. Highlights: The study examines the impact of inflation, interest rates, and exchange rates on the Composite Index (JCI) using empirical analysis. Interest rates are found to have a positive and significant effect on the JCI, while exchange rates show a negative and significant impact. The simultaneous presence of inflation, interest rates, and exchange rates has a significant influence on the JCI, providing insights for investors and policymakers. Keywords: Inflation, Interest Rates, Exchange Rates, Composite Index, Empirical Analysis.